EXPLORING THE LEAF ANATOMY OF LOCAL MEDICINAL PLANTS AND ITS APPLICATION AS MICROSCOPIC LEARNING MATERIAL - Rosma, Fatemah; Hasanah, Mauizah; Suwarniati, Suwarniati; Fadhila, Arief (Prodi Tadris Biologi Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2025)
This study aims to describe the anatomical variations of leaves from five local medicinal plant species and evaluate their potential use as microscopy-based learning media rooted in local wisdom. Microscopic observations were conducted on the leaves of Piper betle, Cymbopogon citratus, Curcuma longa, Aloe vera, and Ocimum sanctum using fresh-section preparations and quantitative measurements of anatomical parameters, including epidermal thickness, mesophyll thickness, stomatal density, trichome characteristics, stomatal type, palisade–spongy ratio, xylem diameter, and vein density. The results revealed clear interspecific anatomical differences, such as variations in palisade structure, presence of secretory ducts, mucilaginous cells, and glandular trichomes that provide strong visual contrast for microscopic learning. These characteristics support the feasibility of using local plant species as accessible, contextually relevant, and effective learning media to enhance students’ understanding of plant anatomy concepts. The study concludes that local medicinal plants possess strong potential to be developed as authentic microscopy learning resources. Further research is recommended to expand the number of species examined, incorporate supporting physiological analyses, and develop ready-to-use instructional modules for educators.